A data accuracy evaluation strategy to improve the representation of potential pesticide use areas for endangered species assessments. (17th March 2022) - Frank, Ashlea; Ghebremichael, Lula; Duzy, Leah; Jones, Chad; Brain, Richard; Burd, Tony
Abstract: The use of "best available data" is a fundamental requirement for all scientific forms of analysis. This paper discusses ways to improve the accuracy of data used to evaluate the potential impacts of pesticides on species that are listed as threatened or endangered under the Endangered Species Act (ESA) by ensuring the best available spatial data representing pesticide use sites are applied correctly. A decision matrix is presented that uses accuracy information from metadata contained in the US Department of Agriculture's (USDA's) Cropland Data Layer (CDL) and the Census of Agriculture (CoA) to improve how labeled pesticide use sites are spatially delineated. We suggest recommendations for the current pesticide evaluation process used by the US Environmental Protection Agency (USEPA) and subsequently by the US Fish and Wildlife Services and National Marine Fisheries Service (collectively known as the Services) in Section 7 consultation activities. The decision matrix is applied to each cultivated land layer in the USDA's CDL with recommendations for how best to use each layer in the evaluation process. Application of this decision matrix will lead to improved representation of labeled uses and more accurate overlap calculations used in the assessment of potential impacts of pesticides on endangered species. Integr Environ Assess Manag 2022;18:1655–1666. © 2022 SETAC KEY POINTS: This paper discusses ways to improve the accuracy of data used to evaluate the potential impacts of pesticides on species that are "listed" as threatened or endangered under the Endangered Species Act by ensuring the best available spatial data representing pesticide use sites are applied correctly. A decision matrix is presented that uses accuracy information from metadata contained in US Department of Agriculture's Cropland Data Layer and the Census of Agriculture to improve how labeled pesticide use sites are spatially delineated.